PCM-Filled Capsules (RT44HC) for Heat Storage—Laboratory Scale Pilot Study - Łukasz Amanowicz; Michał Turski (Energies)
Peak power shaving in heating systems can be achieved using heat accumulators, traditionally implemented in the form of water storage tanks. Their heat capacity can be increased by using a phase change material (PCM) instead of water, which, however, usually requires a change in the tank design. The innovation of this paper is an interesting concept to use plastic capsules filled with a PCM that replace part of the water volume in an existing heat accumulator. The aim of this paper is to compare the cooling rate of the same volume of water as that of the water mixed with the PCM capsules to initially verify the heat storage potential of the capsules. The results of pilot experimental studies on a laboratory scale are presented and discussed, showing the potential of this idea for heat storage. The partial replacement of water with capsules (40% of the total volume) results in significantly faster heat accumulation with the same tank volume (3.85 times at the beginning of the process) and more heat stored (decrease in the temperature of water alone by 14 K and water with PCM capsules by 26 K in the same period of time), which gives promising perspectives for the use of this solution on a semitechnical scale and further in a real-size heating system.